Zakat Ayam Petelur dalam Perspektif Hukum Positif dan Hukum Islam: The Laying Hen ZakaT in Perspective of Positive and Islamic Law - Muhamad Aji Purwanto; Setiawan (Qawanin: Jurnal of Economic Syaria Law, 2022)
This paper discusses the laying of zakat on the perspective of Islamic law and positive Indonesian law. The amount of zakat from zakat mal that must be issued by traders is 2.5% of the amount of assets owned in trade. In the Ngrejo village area, Bakung sub-district, Blitar, there are a lot of successful layers or traders in their business. Social awareness as a Muslim entrepreneur who has an excess of assets makes several laying hens entrepreneurs in Ngrejo village issue their obligations in paying zakat. However, regarding his understanding of the conditions that must be met in issuing zakat, he still does not fully understand. The research method used in this journal is qualitative with a legal approach. Data mining methods used are interviews, observation and documentation. The results showed that several laying hens in Ngerjo Village were aware of their obligation to issue commercial zakat at 2.5% each year. However, in the implementation there are still some aspects that they have not yet understood, such as the class of people who are obliged to be treated. The rest, they have carried out what is their obligation.